Chapter 100 Years of Volkshochschule - 50 Years of DVV International. Local and Global Perspectives on Adult Education and Lifelong Learning - Hinzen, Heribert (Studies on Adult Learning and Education, 2020)
Adult education has multiple histories in countries around the globe. In the case of Germany, the year 1919 is of high importance, as the Volkshochschulen (vhs)-literally translated as folk high schools, more broadly as adult education centres-became a constitutional matter. Today, they are the largest institutionalized form of adult education in Germany with millions of participants every year. In 1969, the ongoing international activities of the vhs were insti-tutionalized into what is known today as DVV International. This year's celebrations are used for contextualizing the development of adult education and thus for remembering the past with a view to the future of our profession.